Universal and Integrable Aspects of an Elliptic Vortex Representation in 2+1‐Dimensional Magneto‐Gasdynamics. Issue 1 (11th July 2012) - Schief, W. K.; An, H.; Rogers, C.
<x xml:space="preserve">Abstract</x> Integrable substructure of a 2+1‐dimensional magneto‐gasdynamic system is investigated via a general elliptic vortex ansatz. Certain universal and Hamiltonian aspects of the admitted representation are uncovered. A class of confined magneto‐gasdynamic flows with an elliptic cylindrical boundary is isolated with time‐dependent semiaxes determined by an integrable Ermakov–Ray–Reid system.